TECHNOLOGIES OF TISSUE ENGINEERING AND REGENERATIVE MEDICINE - V. I. Sevastianov (Вестник трансплантологии и искусственных органов)
The paper presents the main fundamental and applied results obtained by the Department of Biomedical Technologies and Tissue Engineering over the period of 2010–2014.